Revision of the genus ceriantheomorphe (Cnidaria, anthozoa, ceriantharia) with description of a new species from the gulf of Mexico and northwestern Atlantic - Lopes, Celine S. S. [UNESP]; Ceriello, Hellen [UNESP]; Morandini, André C.; Stampar, Sérgio N. [UNESP] (Pensoft Publishers, 2019)
The present study presents a revision of the genus Ceriantheomorphe Carlgren, 1931, including redescrip-tions of the two presently recognized species, Ceriantheomorphe ambonensis (Kwietniewski, 1898) and Ceriantheomorphe brasiliensis (Mello-Leitão, 1919), comb. nov., and a description of the new species Ceriantheomorphe adelita sp. nov.
Keywords: Biogeography; Cnidarian taxonomy; North America; Pacific Ocean; South America